Long-Term Organic Farming Manipulated Rhizospheric Microbiome and Bacillus Antagonism Against Pepper Blight (Phytophthora capsici) - Li, Huixiu; Cai, Xiaoxu; Gong, Jingyang; Xu, Ting; Ding, Guo-chun; Li, Ji (Frontiers in Microbiology, 2019)
Soil-borne diseases are often less severe in organic farms, possibly because of the recruitment of beneficial microorganisms by crops. Here, the suppressiveness of soils from organic, integrated, and conventional farming systems to pepper blight (Phytophthora capsici) were studied in growth chamber experiments. Disease incidence was 41.3% and 34.1% lower in the treatment with soil from the organic farming system than either from the integrated or conventional farming system, respectively. Beta-diversity of rhizospheric microbial communities differed among treatments, with enrichment of Bacillus, Sporosarcina, Acidobacteria Gp5, Gp6, Gp22, and Ignavibacterium by the organic soil. Cultivation-dependent analysis indicated that 50.3% of in vitro antagonists of P. capsici isolated from the rhizosphere of healthy peppers were affiliated to Bacillus. An integration of in vitro antagonists and metagenomic analysis indicated that Bacillus antagonists were higher in the rhizosphere of pepper treated by the organic soil. A microbial consortium of 18 in vitro Bacillus antagonists significantly increased the suppressiveness of soil from the integrated farming system against pepper blight. Overall, soil microbiome under the long-term organic farming system was more suppressive to pepper blight, possibly due to Bacillus antagonism in the rhizosphere. This study provided insights into microbiome management for disease suppressions under greenhouse conditions.